Institutions for collaboration in industrial clusters: proposal of a per-formance and change management model - Luiz C. R. Carpinetti; Rafael H. P. Lima (International Journal of Production Management and Engineering)
This paper proposes a performance and change management model for institutions for collaboration (IFCs) in industrial clusters to assist them while planning, conducting and evaluating joint actions. A three-stage implementation scheme and a self-assessment tool that helps an IFC determine its compliance with the proposed model are also introduced. The self-assessment tool was applied in three Brazilian IFCs from different clusters. It was found that the IFCs researched face major difficulties in designing and implementing performance measures to evaluate the results and impacts of joint actions. However, IFCs have been successful in identifying local infrastructure and devising informal strategic plans.